Effects of Global Decline in Oil Price on the Financial Performance of selected Deposit Money Banks in Nigeria. - Osuma, Godswill Osagie; Babajide, Abiola Ayopo; Ikpefan, Ochei Ailemen; Nwuba, Emeka Bennett; Jegede, Pelumi Wuraola (International Journal of Energy Economics and Policy, 2019)
The global decline in oil price have had a significant effect on the Nigerian economy especially the banking sector and this has led to some banks; revenue shortfalls, increase in their non-performing loans, layoff of staff, decrease in the bank deposit base, deterioration of the bank’s asset quality, reduction in the banks ticket transactions e.tc. Therefore, the main objective of this research is to examine the effects of the global decline in oil price on the Nigerian banking sector. Descriptive statistics and Simple linear regression was used as a tool for data analysis which was run with a pool ordinary least square (OLS) and the findings revealed that there exists a positive and significant relationship between oil prices and the financial performance (three key performance index were used to measure performance such as; profit after tax, current ratio, and net interest margin) of the banks especially in the period characterized by the decline in oil price. This paper, therefore, recommends that the government should take proactive steps to revamp the Agricultural sector by empowering our local farmers while commercial farming should be encouraged. Banks should endeavor to imbibe diversification of their investments and engage in financial innovation in other to improve their performance so as to enable them to be competitive globally. Keywords: Oil price, Syndicated loans, Oil and gas sector, Profitability, Deposit money banks JEL Classifications: Q40, Q43, G21 DOI: https://doi.org/10.32479/ijeep.7514